Studies on the Interleukin-10 Gene in Animal Models of Colitis - Hugh J Freeman (Canadian Journal of Gastroenterology)
Cytokines play a role in the inflammatory process in colitis and may have therapeutic potential. Interleukin-10 (IL-10) has both immunomodulatory and anti-inflammatory properties. IL-10-deficient mice develop intestinal inflammation with increased tissue levels of other cytokines, including tumour necrosis factor-alpha. In patients with inflammatory bowel disease, impaired IL-10 production by lamina propria T cells occurs and human recombinant IL-10 improves clinical parameters in inflammatory bowel disease (eg, Crohn's disease). There seem to be conflicting results in differing animal models, and the timing of administration of IL-10 relative to onset of colitis may be critical, possibly due to rapid clearance of IL-10. Interestingly, in IL-10 gene-deficient mice raised in germ-free conditions, the intestinal inflammatory changes normally observed in conventional nongerm-free conditions are not detected, suggesting a role for luminal bacteria in the pathogenesis of the inflammatory process.